Development of Magnetic Numbers Book Media to Introduce the Concept of Numbers to Children Aged 5-6 Years - Nindy Dwi Kurniasih; Suningsih, Taruni (Yayasan Corolla Education Centre, 2025)
The purpose of this study is to validate the validity and usefulness of the Magnetic Numbers Book, a learning tool for teaching number concepts to children ages 5 to 6. This study uses Tessmer's formative assessment in conjunction with the ADDIE paradigm (Analyze, Design, Development, Implementation, Evaluation) as part of the Research and Development (R&D) approach. Techniques for gathering data include observations and walkthroughs. The instrument used includes an observation sheet based on indicators such as number recognition, number-symbol matching, grouping, and classification. These indicators are derived from the cognitive development standards for children aged 5–6 years. The collected data were analyzed quantitatively by calculating the percentage scores from expert validations and observational assessments during one-to-one and small group evaluations. During the expert review phase, the average validation score was 93% (highly valid), with media experts scoring 97% (very valid) and material experts scoring 89% (highly valid). In the one-to-one evaluation stage involving three children, the observation results indicated a practicality score of 93% (highly practical), whereas in the small group evaluation stage with nine children, the observation score reached 97% (highly practical). Based on the research findings, the Magnetic Numbers Book is deemed highly valid and highly practical, making it suitable for use in the learning process for children aged 5–6 years.